2021
DOI: 10.2196/29642
|View full text |Cite|
|
Sign up to set email alerts
|

Stepwise-Hierarchical Pooled Analysis for Synergistic Interpretation of Meta-analyses Involving Randomized and Observational Studies: Methodology Development

Abstract: Background The necessity of including observational studies in meta-analyses has been discussed in the literature, but a synergistic analysis method for combining randomized and observational studies has not been reported. Observational studies differ in validity depending on the degree of the confounders’ influence. Combining interpretations may be challenging, especially if the statistical directions are similar but the magnitude of the pooled results are different between randomized and observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although not as rigid as the pooled analysis of randomised controlled trials, the pooled results of studies with reliable comparability have very low heterogeneity and are consistently valid, increasing the reliability of hypothesis testing. 15 Although both RFA and ablative RT confer a high LC probability for small intrahepatic malignancies, RFA might yield suboptimal LC for tumours near major vessels or the diaphragm, or those exceeding 2–3 cm in size. 9 , [45] , [46] , [47] However, ablative RT is less limited by tumour location because it does not cause mechanical damage and can provide a prescribed dose within a relatively wide range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not as rigid as the pooled analysis of randomised controlled trials, the pooled results of studies with reliable comparability have very low heterogeneity and are consistently valid, increasing the reliability of hypothesis testing. 15 Although both RFA and ablative RT confer a high LC probability for small intrahepatic malignancies, RFA might yield suboptimal LC for tumours near major vessels or the diaphragm, or those exceeding 2–3 cm in size. 9 , [45] , [46] , [47] However, ablative RT is less limited by tumour location because it does not cause mechanical damage and can provide a prescribed dose within a relatively wide range.…”
Section: Discussionmentioning
confidence: 99%
“…The stepwise-hierarchical pooled analysis by Shin et al. 15 was referred to for the stepwise analysis methods and interpretation of the subject owing to scarce randomised literature. Subgroup analyses were also performed according to the disease, including HCC and colorectal cancer (CRC) with liver metastases.…”
Section: Methodsmentioning
confidence: 99%
“…We performed sensitivity analyses including randomized studies only, as well as pooled analyses including all studies that met the inclusion criteria. For the integrated interpretation of the pooled results of the overall and sensitivity analyses, we referred to the stepwise hierarchical pooled analysis for synergistic interpretation by Shin and Rim 18 (i.e. the ascending pattern of effect size, statistical significance, and validity of subgroups strengthens the hypothesis, whereas the descending pattern weakens).…”
Section: Methodsmentioning
confidence: 99%
“…Since the included studies dealt with heterogenous primary sites, subgroup analyses per primary were also subsequently performed. Subgroup analyses were performed according to hierarchical comparability and study designs, as suggested by Shin and Rim [ 14 ].…”
Section: Methodsmentioning
confidence: 99%